1996
DOI: 10.1002/(sici)1097-0215(19960301)65:5<627::aid-ijc12>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

rho-mediated protein tyrosine phosphorylation in lysophosphatidic-acid-induced tumor-cell invasion

Abstract: Rat ascites hepatoma cells (MM I) invade a mesothelial cell monolayer in vitro inassay medium containing serum, but not in serum-free medium. Serum could be completely replaced by I -oleoyl lysophosphatidic acid (LPA) in inducing invasion. LPAinduced invasion was inhibited by genistein, a tyrosine-kinase inhibitor. Protein tyrosine phosphorylation in response to LPA was thus analyzed in order to determine the molecular mechanism of invasion. LPA of invasion-inducible concentrations evoked a transient increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 17 publications
2
42
0
Order By: Relevance
“…Although the rho genes have been suspected to be involved in cell transformation, there are few reports about rho gene expressions in human tumour tissues. Recently, in vitro assay revealed that activated RhoA protein is necessary for the motility of keratinocytes induced by hepatocyte growth factor (Takaishi et al, 1994) and that the invasive activity of rat MM 1 cells across the mesothelial cell monolayer is inhibited by Clostridium boturinum exo-enzyme C3 that specifically inactivates Rho proteins (Imamura et al, 1996). Serum-dependent invasional activity of hepatoma cells is regulated by activated RhoA protein (Yoshioka et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Although the rho genes have been suspected to be involved in cell transformation, there are few reports about rho gene expressions in human tumour tissues. Recently, in vitro assay revealed that activated RhoA protein is necessary for the motility of keratinocytes induced by hepatocyte growth factor (Takaishi et al, 1994) and that the invasive activity of rat MM 1 cells across the mesothelial cell monolayer is inhibited by Clostridium boturinum exo-enzyme C3 that specifically inactivates Rho proteins (Imamura et al, 1996). Serum-dependent invasional activity of hepatoma cells is regulated by activated RhoA protein (Yoshioka et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Signal transduction cascades mediated by Rho GTPases originate via the extracellular stimulation of transmembrane receptors such as G protein-coupled receptors (GPCRs), 4 receptor tyrosine kinases, cytokine receptors, and integrins. Of the 22 human Rho family members, RhoA, Rac1, and Cdc42 are the most characterized, stemming from their ability to induce striking changes in cellular morphology upon activation (3).…”
mentioning
confidence: 99%
“…These events have been demonstrated to occur downstream of RhoA and to be closely involved in transcellular migration. 20,21,24 Moreover, because anti-fibronectin (FN) antibodies (Abs), anti-␤1 integrin Abs and cyclo-GRGDSPA remarkably suppressed LPAinduced migration, the interaction between FN and ␤1 integrin is also necessary for LPA-induced migration of MM1 cells. 25 These findings show that both LPA-induced activation of the RhoA-ROCK pathway and integrin signaling via the FN-␤1 integrin interaction are essential and that paxillin may play an important role in integrating both signals into the migration of MM1 cells.…”
mentioning
confidence: 99%